Prevalence and distribution of Taenia solium cysticercosis in naturally infected pigs in Punjab, India - Singh, Satinder Pal; Singh, Balbir Bagicha; Kalambhe, Deepali G.; Pathak, Devendra; Aulakh, Rabinder Singh; Dhand, Navneet K. (PLOS Neglected Tropical Diseases, 2018)
Author summary Taenia solium cysticercosis is a neglected zoonosis and severely affects pork production and public health in India. The current study was conducted to estimate the prevalence and distribution of T. solium porcine cysticercosis in the Punjab state of India and to compare the disease prevalence in pigs reared within and outside Punjab. Overall, 24 of the 1132 inspected pigs had viable cysts. Imported pigs had significantly higher prevalence than the pigs produced locally. The analysis did not indicate the presence of T. asiatica in the slaughter pigs. The study confirms the endemic nature of T. solium cysticercosis in Punjab state of India and provides suggestions about reducing the disease burden in pigs and the public.